Management of Orofacial Manifestations of Juvenile Idiopathic Arthritis: Interdisciplinary Consensus‐Based Recommendations. Issue 1 (25th November 2022) - Stoustrup, Peter; Resnick, Cory M.; Abramowicz, Shelly; Pedersen, Thomas K.; Michelotti, Ambra; Küseler, Annelise; Koos, Bernd; Verna, Carlalberta; Nordal, Ellen B.; Granquist, Eric J.; Halbig, Josefine Mareile; Kristensen, Kasper D.; et al.
Abstract : Involvement of the temporomandibular joint (TMJ) is common in juvenile idiopathic arthritis (JIA). TMJ arthritis can lead to orofacial symptoms, orofacial dysfunction, and dentofacial deformity with negative impact on quality of life. Management involves interdisciplinary collaboration. No current recommendations exist to guide clinical management. We undertook this study to develop consensus‐based interdisciplinary recommendations for management of orofacial manifestations of JIA, and to create a future research agenda related to management of TMJ arthritis in children with JIA. Recommendations were developed using online surveying of relevant stakeholders, systematic literature review, evidence‐informed generation of recommendations during 2 consensus meetings, and Delphi study iterations involving external experts. The process included disciplines involved in the care of orofacial manifestations of JIA: pediatric rheumatology, radiology, orthodontics, oral and maxillofacial surgery, orofacial pain specialists, and pediatric dentistry. Recommendations were accepted if agreement was >80% during a final Delphi study. Three overarching management principles and 12 recommendations for interdisciplinary management of orofacial manifestations of JIA were outlined. The 12 recommendations pertained to diagnosis (n = 4), treatment of TMJ arthritis (active TMJ inflammation) (n = 2), treatment of TMJ dysfunction and symptoms (n = 3), treatment of arthritis‐related dentofacial deformity (n = 2), and other aspects related to JIA (n = 1). Additionally, a future interdisciplinary research agenda was developed. These are the first interdisciplinary recommendations to guide clinical management of TMJ JIA. The 3 overarching principles and 12 recommendations fill an important gap in current clinical practice. They emphasize the importance of an interdisciplinary approach to diagnosis and management of orofacial manifestations of JIA.